The Influence of The Role of Field Agricultural Extension Workers (PPL) as Mediators on The Success of The Rural Agribusiness Business Development Program (PUAP) - Siti Aisyah; Achmad Faqih; Subandi Subandi; Khambali Khambali; Taswa Wijaya Kusuma; Isyanto Isyanto (Pusat Publikasi Nusantara, 2023)
The role of extension workers as mediators can be measured from indicators that connect information sources with farmers, problem-solving processes, and farmers' needs. The role of field agricultural extension workers (PPL) as mediators for the success of the PUAP program is certainly very important because field agricultural extension workers are responsible for conveying information on programs held by the Cirebon Regency government for farmers. This study aims to determine the influence of the role of field agricultural extension workers as mediators on the success of the PUAP program. The research design used in this study is descriptive quantitative research with census sample research techniques. The population used, namely the Sijaba farmer group, is in Pasanggrahan Village, Plumbon District, Cirebon Regency. The section examined was on the effect of the role of field agricultural extension workers (PPL) as mediators on village PUAP programs. The number of samples used was 59 respondents with census sampling techniques. The research was conducted in October – December 2022. The data analysis technique uses a simple linear regression test. Based on the results of the research and discussion that has been described, it can be concluded that the role of field agricultural extension workers (PPL) as mediators has a positive effect on the success of the PUAP program in Pasanggrahan Village, Plumbon District, Cirebon Regency